The Influence of Cyberloafing on Employee Performance at the Cooperatives and SMEs Office of South Sulawesi Province - Aqilla Fadia Herman; Haedar Akib; Sirajuddin Saleh; Andi Muhammad Rivai (Business Research and Administration Innovation, 2024)
The Effect Cyberloafing on Employee Performance at the Cooperatives and SMEs Service Office of South Sulawesi Province. Thesis. Business Administration Science Study Program. Department of Administrative Sciences. Faculty of Social Sciences and Law, Makassar State University. (supervised by Haedar Akib and Sirajuddin Saleh). This study aims to find out how the description and whether there is an effect cyberloafing on the performance of employees at the Cooperatives and SMEs Service Office of South Sulawesi Province. To achieve this goal, the researchers used indicators to measure these variables.variable cyberloafing , the indicators used are e-mailing activity and browsing activity. As for the employee performance variables using indicators of quality, quantity, timeliness, effectiveness and independence. This study uses quantitative research methods. Data collection techniques used are through observation, questionnaires and documentation. The population in this study were all employees at the secretariat of the Department of Cooperatives and SMEs of South Sulawesi Province which consisted of three sub. section namely sub. general section, staffing and law, sub. finance and sub. part of the program totaling 38 people. The sampling technique used in this study is the Krejcie table, which is 36 respondents. The data obtained from the research results were processed using data analysis and SPSS 25 application which consisted of validity and reliability tests, descriptive statistical data analysis techniques and inferential statistical analysis. The results of this study indicate that the indicators used in each cyberloafing and employee performance are in the quite and very good categories. Based on the determinant coefficient test, there is a very small effect between the two variables, which is 16.3%. Based on the simple linear regression coefficient, it shows a negative value, so it can be said that the direction of the influence of the variable X on Y is negative. So, it can be concluded that there is a significant negative effect between cyberloafing on employee performance.